Os efeitos da intranet na comunicação organizacional no contexto da complexidade: um estudo de caso - Vailati Neto, Henrique (2005)
The proposal of this dissertation is to identify, to analyze and to reflect the use of the Technologies of the Communication and Information in the processes of organizational communication in the scope of the Theory of the Complexity in order to search, to little in latency, the structural corollaries of technological innovations that, in general way, had still not been analyzed in the ratio and intensity of the general volume of the changes and the material efforts already expensed in it, over all to what refers to aspects of the organizational culture. To base our hypotheses, in we support them in a study of case of implantation of an Intranet, or either, of a corporative vestibule. For in such a way, in we are valid them the some of most consistent studious of the virtual space, as Pierre Lévy and of the thinkers of the Theory of the Complexity while cloth of deep theoretician who could confer to our reflections the enough methodological sustentation in allowing to think the organizations in the difficult framing and dynamics of this moment of mutations and imprevisibility.